Biomechanical Comparison of Six Different Root-Analog Implants and the Conventional Morse Taper Implant by Finite Element Analysis - Wang, Jia-Qing; Zhang, Yuan; Pang, Min; Wang, Yue-Qiu; Yuan, Jun; Peng, Hui; Zhang, Wen; Dai, Lu; Li, Hong-Wei (Frontiers in Genetics, 2022)
Taper implants differ greatly from anatomical teeth in shape. In this study, Seven three-dimensional finite element models were established, including a conventional taper implant and six root-analog implants with different root numbers and shapes. Vertical, horizontal, and oblique instantaneous loads of 100 N were applied to the models to obtain stress distribution in the implant, mucosa, cortical bone, and cancellous bone. ANSYS was used to perform the analysis under hypothetical experimental conditions. We find the stresses in all implants and surrounding tissues varied by loading direction, the sequence of stress magnitude is vertical load, oblique load, then horizontal load. The maximum stress values in root-analog implants were significantly less than in the taper implant; moreover, stress distribution in the former was equalized contrary to the concentrated stress in the latter. Root-analog implants with different root geometry also revealed a pattern: stresses in multiple-root implant models were lower than those in single-root implants under the same load. The implant with a long and rounded root distributed the stress more uniformly, and it was mainly concentrated on the implant itself and cancellous bone. However, the opposite effect was observed in the short implant on mucosa and cortical bone. The root geometry of anatomical teeth can modify their functions. A uniform-shaped implant can hardly meet their functional requirements; thus, the root-analog implant could be a possible solution.